DOCUMENTOS ARQUIVÍSTICOS, CENTROS DE MEMÓRIA, ORGANIZAÇÃO E INSTITUIÇÃO: caminhos potenciais para os trabalhos com memória na Justiça Eleitoral - Rodrigo Costa Japiassu (TRF2, 2020)
The present work retrieves and expands reflections presented in a master's dissertation regarding the memorial works carried out from archival documents in memory centers in the Brazilian Federal Judiciary (PJF) -now focused on Electoral Justice. The understanding of archival documents is re-signified, in the light of archival and organizational theories. The characterization of electoral memory is made in comparison to the notion of institutional memory and, further, understanding the regulatory function of Electoral Justice. Bibliographic research was used to talk about organization, institution and institutionalization processes. The comparative method was used to recover archival and organizational / institutional aspects related to the archival document, as well as to develop the notion of electoral memory based on institutional memory. It is concluded that there is still an enormous potential to be explored for the uses of the archival document as a semiophore institutionalized by the bodies of theElectoral Justice, allowing interactions even of social sectors with which this specialized branch of the Federal Judiciary is involved relates.